Pengaruh Biaya Transportasi, Jarak ke Fasilitas Kesehatan, dan Intensitas Pengguna PBI JKN terhadap Beban Out-Of-Pocket Masyarakat Miskin di Kabupaten Lebak - Zevi Ardiansyah Saputra; Ida Ayu Meisthya Pratiwi (Lembaga Pengembangan Kinerja Dosen, 2026)
Health is a fundamental right guaranteed by the state; however, poor communities still face significant challenges in financing healthcare due to high out-of-pocket (OOP) expenditures. According to the 2022 National Health Accounts (NHA) data, the OOP proportion in Indonesia reached 30.6% of total national health expenditures—exceeding the World Health Organization (WHO) safety threshold of 20%. This condition indicates that the financial burden of healthcare remains heavy, particularly for low-income groups, even though they are beneficiaries of the National Health Insurance – Contribution Assistance Recipients (Jaminan Kesehatan Nasional – Penerima Bantuan Iuran or JKN-PBI). The National Socioeconomic Survey (SUSENAS) of March 2024 revealed that 51.20% of residents in Banten Province who experienced health complaints chose not to seek treatment, citing transportation costs and the long distance to healthcare facilities as primary reasons. These non-medical barriers further exacerbate the OOP burden among the poor. This study aims to analyze the influence of transportation costs, distance to healthcare facilities, and the intensity of JKN-PBI utilization on the out-of-pocket burden of poor households in Lebak Regency. The study population consists of JKN-PBI participants in Guradog Village, Curugbitung District, with a total sample of 160 respondents selected through purposive sampling. Data were analyzed using multiple linear regression with the SPSS software. The results show that, simultaneously, transportation costs, distance, and JKN-PBI utilization intensity have a significant effect on OOP. Partially, transportation costs and distance have a positive and significant effect, while JKN-PBI utilization intensity has a negative and significant effect. This study emphasizes the importance of equitable access to healthcare facilities, transportation subsidies for JKN-PBI participants in remote areas, and the enhancement of JKN utilization.